2006
DOI: 10.1529/biophysj.106.083766
|View full text |Cite
|
Sign up to set email alerts
|

Cubic Phases in Phosphatidylcholine-Cholesterol Mixtures: Cholesterol as Membrane “Fusogen”

Abstract: X-ray diffraction reveals that mixtures of some unsaturated phosphatidylcholines (PCs) with cholesterol (Chol) readily form inverted bicontinuous cubic phases that are stable under physiological conditions. This effect was studied in most detail for dioleoyl PC/Chol mixtures with molar ratios of 1:1 and 3:7. Facile formation of Im3m and Pn3m phases with lattice constants of 30-50 nm and 25-30 nm, respectively, took place in phosphate-buffered saline, in sucrose solution, and in water near the temperature of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
86
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 54 publications
2
86
1
Order By: Relevance
“…[36,37] However, the small circular contact interface between the vesicles enforces bending of the elongated stalk along its perimeter and restricts its topology to that of an inverted micelle. Due to the inherent relation with inverse lipid phases, the formation of IMIs is expected at, for example, a high PE and/or cholesterol content [38,39] or for membranes that are moderately enriched with anionic lipids in the presence of calcium. [40,41] This has readily been observed in simulations for experimentally feasible 1:1 PC/PE mixtures.…”
Section: ) Formation Of An Inverted Micelle Intermediate (Imi)mentioning
confidence: 99%
“…[36,37] However, the small circular contact interface between the vesicles enforces bending of the elongated stalk along its perimeter and restricts its topology to that of an inverted micelle. Due to the inherent relation with inverse lipid phases, the formation of IMIs is expected at, for example, a high PE and/or cholesterol content [38,39] or for membranes that are moderately enriched with anionic lipids in the presence of calcium. [40,41] This has readily been observed in simulations for experimentally feasible 1:1 PC/PE mixtures.…”
Section: ) Formation Of An Inverted Micelle Intermediate (Imi)mentioning
confidence: 99%
“…Cholesterol is one of such molecules due to its ability to modify bilayer fluidity [83]. Inclusion of cholesterol results in the formation of complexes that are more stable but less efficient in vitro compared to DOPEcontaining lipoplexes.…”
Section: Role Of Mo As Helper Lipid In Pdna/dodab/mo Lipoplexesmentioning
confidence: 99%
“…However, in our case, other space groups can not be ruled out with certainty since only few of the allowed reflections could be observed. Metastability and difficulties in reproducibility of bicontinuous phases, where kinetic factors seem to play an important role, have been frequently noted in the literature [88,146,147,148]. This could explain why the appearance of pattern C depended on the protocol for thermal equilibration prior to the measurements.…”
mentioning
confidence: 99%
“…All observed peaks are accounted for if a body-centered cubic lattice (symmetry element I for innenzentriert, reflection condition h +k +ℓ = 2n, n ∈ Z) is assumed. TENCHOV et al observed cubic phases in aqueous dispersions of DOPC/Chol mixtures which were subject to heating/cooling cycles by powder diffraction [146]. In their analysis, the strong {211} and {220} reflections corresponding to a ratio of spacings 6 : 8 indicate space group I a3d containing gyroid structures ( Fig.…”
mentioning
confidence: 99%